Woody Gall of Sweet Orange - NOUR-ELDIN, FARID (The Libyan Journal of Agriculture, 2023)
A newly reported woody gall disease affecting demi sweet orange trees was observed in Libya. Woody galls develop on the trunks and limbs of the affected trees. This abnormality was bud-transmitted to young trees of demi sweet orange. Galls developed on the inoculated trees at the bud-union. Bud-inoculated Mexican lime seedlings did not develop vein-enation.